Astrocytes: Heterogeneous and Dynamic Phenotypes in Neurodegeneration and Innate Immunity. (October 2019) - Cunningham, Colm; Dunne, Aisling; Lopez-Rodriguez, Ana Belen
Astrocytes are the most numerous cell type in the brain and perform several essential functions in supporting neuronal metabolism and actively participating in neural circuit and behavioral function. They also have essential roles as innate immune cells in responding to local neuropathology, and the manner in which they respond to brain injury and degeneration is the subject of increasing attention in neuroscience. Although activated astrocytes have long been thought of as a relatively homogenous population, which alter their phenotype in a relatively stereotyped way upon central nervous system injury, the last decade has revealed substantial heterogeneity in the basal state and significant heterogeneity of phenotype during reactive astrocytosis. Thus, phenotypic diversity occurs at two distinct levels: that determined by regionality and development and that determined by temporally dynamic changes to the environment of astrocytes during pathology. These inflammatory and pathological states shape the phenotype of these cells, with different consequences for destruction or recovery of the local tissue, and thus elucidating these phenotypic changes has significant therapeutic implications. In this review, we will focus on the phenotypic heterogeneity of astrocytes in health and disease and their propensity to change that phenotype upon subsequent stimuli.